Risk and crisis management in the public sector - Drennan, Lynn T.; McConnell, Allan (Routledge masters in public management, 2007)
This innovative text aims to provide its readers with the knowledge and skills necessary to assess and treat risks arising in public sector organizations. It also addresses the steps involved in preparing for and dealing with crisis, and how valuable lessons can be learned in the aftermath of such events. Examples are drawn from a range of public sector organizations in Europe and Australasia, with both the UK and AS/NZW risk management standards forming the basis for understanding and implementing the risk management process.